The Effects of Polarization and Non-Linearity on the Performance of WDM System with Optical Cross-Connects - Thiam, Sim Ngee; Rahman, Faidz ABD. (TAYLOR & FRANCIS INC, 2007)
The performance of a wavelength division multiplexing (WDM) system with optical cross-connects (OXCs) and in the presence of polarization and nonlinear effects was analyzed. We determined the effect of PMD and PDL; nonlinearity such as XPM, SPM, and FWM; and CD on the system performance. We found that the system outage probability is highest at DGD threshold for the respective maximum eye closure (EC). We showed that the allowable DGD depends on the time slot for one bit T, which is the inverse of the network bit rate. Wider T is more immune to large PMD with the EC still maintained at the same level since DGD/T is unchanged. Our analysis also indicated that as DGD increases, BER increases. The BER also increases with increase in PDL and further increases with the presence of XPM, SPM, FWM, and CD.